NIR‐II Fluorescence imaging for cerebrovascular diseases. Issue 6 (18th June 2021) - Ren, Feng; Jiang, Zhilin; Han, Mengxiao; Zhang, Hao; Yun, Baofeng; Zhu, Hongqin; Li, Zhen
Abstract: As the major pipeline for transporting oxygen and nutrients to living tissues, well‐ordered and functional vasculature is vital to maintain the function of organisms. The cerebrovascular disorders induced by acute or chronic diseases, including traumatic brain injury (TBI), stroke, and brain tumors, could cause vascular cognitive impairment and even mortality. Due to the complication of these cerebrovascular diseases, early diagnosis and monitoring their pathological processes in real time in animal models could enlighten us with insights into early prevention and effective treatment. Over the last decade, the NIR‐II fluorescence imaging technology has been well developed in both nanofluorophores and imaging systems. For cerebrovascular disorders, the collaborative use of wide‐field imaging setup with NIR‐II nanoprobes enable arteriovenous staging, and calculation of blood flow velocity to distinguish ischemic area in TBI and stroke. The changes in molecular and cellular levels of TBI provide the guidance on the design of targeted and activatable NIR‐II nanoprobes for evaluating and monitoring the microenvironment variations. For the brain tumors, both targeted strategy and focus ultrasound sonication are efficient approaches for overcoming the blood‐brain‐barrier and brain‐tumor‐barrier for delivery of nanoprobes. Therefore, NIR‐II fluorescence imaging‐guided surgical navigation of brain tumors and resected lesions biopsy intraoperatively ensure the accuracy of surgery based on the precise definition of tumor margins. This review summarizes the recent advances in NIR‐II fluorescence imaging technology, which is mainly inclusive of well‐developed NIR‐II nanofluorophores and their applications in cerebrovascular diseases with address of its challenges and great potential in these aspects. Abstract : Recent advances in the NIR‐II fluorescence imaging of cerebral diseases inclusive of stroke, TBI, cerebroma at multilevels of tissue, cell, and molecule by using inorganic and organic nanoprobes are comprehensively reviewed.